Collision-induced light scattering (CILS) and collision-induced absorption (CIA) spectra for monatomic rare gas mixtures. (July 2019) - Godet, J.-L.; El-Kader, M.S.A.
Highlights: Isotropic interatomic potentials of the inert gas mixtures Ne-Ar and Kr-Xe are determined. The thermo-physical properties are calculated for these systems. The collision-induced absorption spectra at different temperatures are determined. The different forms of induced trace and anisotropy polarizabilities are used for mixtures. The isotropic and depolarized spectra are calculated at room temperature. Abstract: The isotropic and anisotropic collision-induced light scattering (CILS) for gaseous binary mixtures of neon with argon and krypton with xenon are computed using pair polarizabilities trace and anisotropy as input. Also the line shapes of collision-induced absorption (CIA) at different temperatures are determined using theoretical induced dipole moment and interatomic potential. Comparison with measured scattering and absorption spectra and literature shows a good agreement, despite the uncertainty about spectral moments. Good agreement between computed and experimental line shapes of scattering and absorption is also obtained when potential models which are constructed from the thermo-physical and transport properties are used. Graphical abstract: Image, graphical abstract